Determination of Critical Stresses in Frozen Soils Under Wave Acoustic Loading - Chebotarev, Yu.I.; Korepina, N.A.; Verkhoturov, V.V. (Iraqi Journal of Science, 2022)
The issues related to the development of permafrost and seasonally frozen soils without their preliminary loosening by various earthmoving machines with active working bodies, magnetostrictive vibrators, that soften dense and frozen soils using acoustic elastic waves, are considered. The analytical studies allowed us to establish the regularities of the process of destruction of frozen soil by active teeth of bucket working bodies, according to which, the formulas for calculating the critical tensile stress and shear resistance were obtained. The research results allow us to determine the main parameters of wave loading for both a single radiation source and a group of "n" in-phase radiation sources. The intensity of the acoustic field from the group of "n" emitters increases in proportion to the number of vibration exciters.